Ribosomal Mutations Conferring Resistance to Macrolides in Streptococcus pneumoniae Clinical Strains Isolated in Germany - Reinert, Ralf René (American Society for Microbiology, 2003)
Among a collection of 4,281 pneumococcal isolates, 7 strains isolated in Germany had an unusual macrolide resistance phenotype. The isolates were found to have multiple mutations in the 23S rRNA and alterations in the L4 ribosomal protein. One strain had an amino acid alteration in the L22 ribosomal protein.